2022
DOI: 10.1039/d2ma00785a
|View full text |Cite
|
Sign up to set email alerts
|

Interlocking dendritic fibrous nanosilica into microgranules by polyethylenimine assisted assembly: in situ neutron diffraction and CO2 capture studies

Abstract: Solid amine-based nano-adsorbents have shown tremendous potential for mitigating CO2 emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…The time resolution of the spectrometer is described as the sum of two Gaussian functions having the full width at half-maxima of 0.205 (92%) and 0.209 ns (9%), respectively, with 0.186 ns relative shift. A radioactive isotope 22 Na (∼10 μCi) sealed in an envelope of ∼8 μm thick Kapton films was used for the acquisition of the spectra. The source was embedded in the powder sample, ensuring that all the emitted positrons annihilate within the powder sample.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time resolution of the spectrometer is described as the sum of two Gaussian functions having the full width at half-maxima of 0.205 (92%) and 0.209 ns (9%), respectively, with 0.186 ns relative shift. A radioactive isotope 22 Na (∼10 μCi) sealed in an envelope of ∼8 μm thick Kapton films was used for the acquisition of the spectra. The source was embedded in the powder sample, ensuring that all the emitted positrons annihilate within the powder sample.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…In order to further enhance the CO 2 capture efficiency, new strategies are being developed to produce solid sorbents. Among these strategies, evaporation-induced self-assembly of colloids of amine-bearing polymers, e.g., polyethyleneimine (PEI)-assisted silica nanoparticles, is highly apt for the production of highly porous sorbents with amine functionalities. Recently, we have shown that the CO 2 capture efficiency of these microspheres depends on their porosity as well as the loaded amine functionality . The evaporation-induced self-assembly of multicomponent colloids depends on complex interactions among the different components of the colloids. , As a result, the pore network and dynamics of polymers confined in the pore network of microspheres produced through the self-assembly of multicomponent colloids depend on various factors. Hence, it is imperative to investigate the pore architecture and dynamics of confined polymers within the pore network of self-assembled microspheres using complementary techniques. Thus, the obtained knowledge will be crucial for the design of self-assembled microspheres of silica nanoparticles loaded with polymers for their applications in gas storage, gas separation, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…[55] Very recently, Bahadur's team developed novel composite microgranules composed of DMSNs and PEI by an evaporation-induced assembly approach, where PEI incorporated into the pores of DMSNs or onto their surfaces. [56] Small and large microgranules were fabricated with different porosity and interconnectivity, giving rise to significantly improved CO 2 adsorption capacity and kinetics for DMSNs-PEI (Table S2, Supporting Information). Most importantly, in situ neutron scattering as a nondestructive technique was applied for the first time to explore the kinetics of CO 2 adsorption.…”
Section: Amino-functionalized Dmsnsmentioning
confidence: 99%